Effects of food programme for enhancing obesity children healthy of their abilities and expectations to self-efficacy for preventing early childhood - Tanwattanakul, Jirawon; Sriprachote, Suthiporn; Tangpukdee, Juraporn; Chantapreeda, Nilawan; Santiboon, Toansakul Tony (Journal of Advanced Pediatrics and Child Health, 2021)
This study aims to assess parents’ perceptions of their responses to the perceived awareness programme competency abilities and expectations for enhancing parents on weight control of their pre-school children in preventing with Obesity. It has defined self-efficacy as one’s belief in one’s ability to succeed in specific situations and accomplish a task with the theoretical framework of Bandura’s Model by quasi-experimental research in 16 weeks. To promote the self-efficacy and expectations, the 10-item Questionnaire on Self-Efficacy Program, the 22-item Questionnaire on Parents’ Efficacy Interaction, and the 46-item Questionnaire on Parental Expectations assessed parents’ perceptions. A sample size consisted of 14-pre-school children whose age ranged 2-5 years old at the Child Development Demonstration Centre, Khon Kaen University was selected. Providing knowledge, teaching, demonstration, experimentation, and organized activities were organized. Parents’ perceptions of their abilities for controlling children’s weight and height with pre- and post-experimental programmes differentiated, significantly. Parents’ responses to the post performances are over than pre-experiment for the QSEP, the QPEA, and the QPE, differently. They answered and followed up on child management with parents online for 16 weeks, continuously. The obese early childhood at the CDC Demonstration Centre, Faculty of Nursing used the food programme to self-efficacy with their parents taking part and cooperating well in specifying research objectives. There are 2,958,441 children in rural areas are lacking attention, because of food and health problems in the 19,171-Child Development Centres none yet have food programmes to prevent health and hygiene problems. Although Thailand took the next leap forward for its investment in Early Childhood Development through legislation, improved quality services, and social transfer grants for families with young children since 2018.